THERMODYNAMIC SIMULATION AND VALIDATION EXPERIMENT OF NEODYMIUM OXIDE REDUCTION INTO METALLIC NEODYMIUM BY METALLOTHERMIC PROCESS - Isyatun Rodliyah; Andina Septiarani; Hasudungan Erick Mamby; Zulfiadi Zulhan; Cristina Alberia Sitompul (Indonesian Mining Journal, 2018)
Neodymium (Nd) is one of the rare-earth elements (REEs) found in significant amount within monazite and bastnasite minerals. Nd is a ferromagnetic metal that is often used as a material to produce magnet, commonly known as a permanent magnet. Neodymium is alloyed with other metals such as iron and boron to form one of the strongest types of permanent magnet. This research aim is to study the reduction process of Nd-oxide into Nd-metal through the metallothermic process. The Nd metal product is expected to fulfill the material specification for a permanent magnet. Thermodynamics simulation of Nd reduction into its metal was conducted using ITB’s licensed Factsage software. A validation experiment was conducted only to the Nd metal resulting simulation. The simulations involved some parameters, i.e. temperatures (600, 700, 800, 900, 1000, 1100 and 1200 °C), types of fluxes  (CaCl2and Ca(OH)2), composition of the reducing agent (1x, 2x dan 3x of the stoichiometric calculations), types of the reducing agents (Ca and Mg), and types of feeds used (Nd-oxide and Nd-chloride). The thermodynamic simulation shows that Nd metal was produced in a condition where the temperature should be1100-1200 °C using Ca as the reducing agent and CaCl2 as the flux, while the amount of reducing agent has no effect on the resulted product. Validation result of the simulations shows that the Nd metal is formed up to 49% metal in a non-oxidative condition.